IFS\(_α \)-Open Sets in Intuitionistic Fuzzy Topological Space - P. Subbulakshmi; P. Karthiksankar (Modern Advances in Geography, Environment and Earth Sciences Vol. 6, 2021)
The aim of this paper is to introduce the concepts of IFS \(_α\) -open sets. Also we discussed the relationship between this type of Open set and other existing Open sets in Intuitionistic fuzzy topological spaces. Also we introduce new class of closed sets namely IFS \(_α\) -closed sets and its properties are studied.